Efeito da microvibração sobre a produção in vitro de embriões bovinos - Santos, Angelica Camargo dos (Universidade Federal de São Carlos, 2022)
Much effort has been employed to improve the quality of embryos obtained by in vitro production (IVP) given the relevance of this technology to current livestock systems. In this context, dynamic IVP systems have been shown to be beneficial to the embryo once they mimic fluid flows and mechanical forces resulting from the movement of ciliated cells and muscle contraction in the reproductive tract. In the present study we sought to confirm these initial findings as well as assess potential molecular consequences to the embryo by applying microvibration (45 Hz for 5 seconds once per 60 minutes) during both oocyte maturation and embryo culture in cattle. As a result, micro-vibration led to cryotolerant blastocysts as indicated by the lower incidence of apoptosis following vitrification-thawing. Further analyses revealed epigenetic and transcriptional changes in blastocysts derived from the micro-vibration treatment, with a total of 502 differentially expressed genes. Enrichment analyses linked differentially expressed genes to “Oxidative phosphorylation”, “Cytokine-cytokine receptor interaction”, and “Signaling pathways regulating pluripotency of stem cells”. Yet, a metaanalysis indicated that the transcriptional change induced by micro-vibration was not toward that of in vivo-derived embryos. In conclusion, micro-vibration leads to bovine embryos of improved cryotolerance, but caution should be taken given the unclear consequences of epigenetic and transcriptional abnormalities induced by the treatment.
Effect of microvibration on in vitro production of bovine embryos
Keywords: Bovinos; Oócitos; PIVE; Epigenética; RNAseq; Cattle; Oocyte; IVP; Blastocyst; Epigenetic; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::GENETICA